2010
DOI: 10.1097/hjh.0b013e32833c21af
|View full text |Cite
|
Sign up to set email alerts
|

Is leptin involved in phagocytic NADPH oxidase overactivity in obesity? Potential clinical implications

Abstract: These findings show that phagocytic NADPH oxidase activity is increased in obesity and is related to preclinical atherosclerosis in this condition. We also suggest that hyperleptinemia may contribute to phagocytic NADPH oxidase overactivity in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…Fortuno and colleagues demonstrated that phagocytic NADPH oxidase activity was increased in obese subjects ( P  < 0.05) and was related to preclinical atherosclerosis in this condition [17]. Also animal studies have provided interesting results of diet-induced obesity on the NADPH oxidases activity and expression of its subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Fortuno and colleagues demonstrated that phagocytic NADPH oxidase activity was increased in obese subjects ( P  < 0.05) and was related to preclinical atherosclerosis in this condition [17]. Also animal studies have provided interesting results of diet-induced obesity on the NADPH oxidases activity and expression of its subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This effect, however, appears to be lost after prolonged treatment, and in ob/ob mice, leptin reduces markers of oxidative stress. 32 Moreover, although a correlation between the plasma level of leptin and NOX activity in human monocytes was reported, 43 in an experimental model, leptin, different from angiotensin II, does not induce the NADPH oxidase. 29 Moreover, when we determined the effect of leptin on the angiotensin II-induced H 2 O 2 formation of angiotensin II type 1 receptor expressing HUVECs, we observed that leptin completely blocked the angiotensin II-induced reactive oxygen species formation (K. Schröder, 2012, unpublished observation), giving rise to the possibility that the beneficial effect of in vivo leptin on angiotensin II-induced hypertension and endothelial dysfunction are, in part, mediated by NADPH oxidase inhibition.…”
Section: Downloaded Frommentioning
confidence: 99%
“…66 The hormone leptin activates NOX and induces the production of reactive intermediates such as H 2 O 2 and hydroxyl radical. 67 In a rodent model, leptin injection caused higher levels of plasma and urinary lipid hydroperoxide, MDA, isoprostane, and protein carbonyl content compared to levels seen in nontreated controls. 68 In addition, leptin also stimulates the proliferation of monocytes and macrophages and thus promotes the production of proinflammatory cytokines.…”
mentioning
confidence: 99%